Kesalahan Penggunaan Konjungsi pada Karangan Penulisan Bahasa Petunjuk Siswa Kelas Viii SMP N 2 Gatak - Arisanti, Tri, Drs. Yakub Nasucha, M.Hum (2016)
Tri Arisanti. A310120257. ERROR OF CONJUNCTIONS IN THE LANGUAGE ESSAY WRITING INSTRUCTION CLASS VIII SMP N 2 GATAK. Skripsi. Faculty of Teacher Training and Education. Muhammadiyah University of Surakarta. April, 2016. This study has two objectives, 1) to analyze the form of error conjunction coordinative additive and sorting on essay writing instructions language class VIII SMP N 2 Gatak, 2) analyze the level of error in the use of conjunctions coordinative additive and sorting on essay writing instructions language class VIII SMP N 2 Gatak. The method in this research is descriptive qualitative. Data collection technique used documentation techniques, followed by techniques refer to note. Technique authenticity of data used triangulation theory. Data were analyzed using methods match those basic techniques PUP and read many. In the study found error conjunction additives (and and with), and fault sorting conjunctions (then, later, next). The form of error conjunction ad ditives and sorting namely, 1) the use of conjunctions and to express the meaning of sequencing, 2) elimination of conjunctions and, 3) conjunctions and does not incorporate elements of words or clauses, 4) use of conjunctions and and with which should be eliminated, 5) conjunctions and are not connecting element noun, 6) and subsequent removal of conjunctions then, 7) use of conjunctions then that should be eliminated, 8) use of conjunctions and the monotone. Based on the analysis, the highest error rate conjunctions and as much as 72.34% because of the use of conjunctions and to express the meaning of sequencing the activities carried out in the text. Keywords: Conjunction, additives, sorting, text instructions.